Menjelajahi Surga di Bawah 'Wonderful Indonesia' - Aji, Gagas; Widodo, Suko; Aji, Gilang Gusti; Aji, Ganjar Ndaru (Jurnal Spektrum Komunikasi, 2025)
Indonesia, renowned for its diverse cultural heritage and breathtaking natural landscapes, has strategically positioned itself on the global tourism stage through the Wonderful Indonesia branding campaign. This study explores the effectiveness of this campaign in transforming Indonesia into a globally recognized tourism destination. By analyzing key performance indicators such as international tourist arrivals, domestic tourism growth, hotel occupancy rates, and the role of digital platforms, this research provides a comprehensive assessment of the campaign's impact. The findings highlight significant achievements, including increased global brand recognition, economic contributions, and improved digital engagement through social media platforms. However, challenges such as over-tourism, regional disparities, and infrastructure limitations persist, posing risks to long-term sustainability. This study emphasizes the importance of balancing growth with sustainable tourism practices and recommends strategies to optimize future branding efforts. Insights from this research aim to guide policymakers, tourism stakeholders, and marketing professionals in enhancing the effectiveness of destination branding campaigns in emerging economies.